HERMENEUTIKA MA’NA-CUM-MAGHZA SAHIRON SYAMSUDDIN DALAM STUDI HADITS - Hijriyah, Athiyah Laila (Zawiyah: Jurnal Pemikiran Islam, 2024)
The goal of this research is to evaluate Sahiron Syamsuddin's ma'na cum maghza theory of hadith studies. The data for this study, which employs a qualitative methodology and a kind of library research, was obtained from documents taken from books and scientific papers. Data for the study were gathered using documentary methods, and content analysis was used to examine them. The study's findings demonstrate that Sahiron Syamsuddin's theory of ma'na cum Maghza is a technique for interpreting hadith (hadith hermeneutics) in which a mufassir identifies the original and/or literal meaning of history as it was understood by the original audience and then develops that meaning in its (Maghza) significance for modern application. The ma'na cum maghza technique of interpretation cannot be used by just anyone. With the ma'na cum maghza approach, concrete steps in interpretation are carried out in two stages. Finding ma'na, or the text's original meaning, comes first. The maghza (importance of the verse) is determined by the second. It is crucial to teach this technique to the upcoming generation of interpreters so that contextualist interpretation instead of literal-textualist interpretation is produced.